A STUDY ON PULMONARY FUNCTION TEST AMONG PETROL-PUMP WORKERS IN TIRUNELVELI TOWN - A, KALA; S, SUBHALAKSHMI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: In India, automobiles plying on roads are increasing every day. This has led to an increase in petrol-pump stations and an increase in pump workers. Petrol vapors and exhaust from vehicles have ill effects on the respiratory system. Petrol is a complex combination of hydrocarbons. Continuous exposure to petroleum vapours and exhaust from vehicles causes altered respiratory physiology. Methods: This study involved 50 petrol-pump workers (PPWs) with another 50 age-matched healthy adults. Their age, history of past illness, smoking exposure, and working hours were noted. Pulmonary function test was done using a computerized Spirometer to measure various parameters. Results: Parameters of pulmonary function in PPWs have a decline in mean values such as FVC, FEV1, peak expiratory flow rate, FIVC, forced expiratory flow (FEF) (25–75%), peak inspiratory flow, VC, and ERV when compared to the control group. It reflects the development of mixed patterns of lung disease (both obstructive and restrictive). Conclusion: It is suggested that reduction or control measures against air pollution including protective equipment, the future movement toward green fuels, and identifying and protecting susceptible workers occupationally exposed to petrol and diesel fumes would be beneficial to humanity and the ecosystem.